PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN PADA PROGRAM KOTAKU DI KOTA KENDARI - Jumatin Jumatin; Juharsah Juharsah; Yusuf Yusuf; Hartini Hartini; Muhammad Taufik; Valentinus Amstrong TN (Pascasarjana Universitas Halu Oleo, 2020)
The purpose of this study was to determine and analyze the effect of transformational leadership style and work discipline on work motivation and to determine the effect of transformational leadership style and work discipline on employee performance of KOTAKU Program in Kendari City. This type of research is explanatory research with sample is 31 employees in KOTAKU Program in Kendari City. Data were collected using a questionnaire and analyzed using SmartPLS.The results of this study indicate that (1) transformational leadership style has a positive and significant effect on employee performance. (2) transformational leadership style has a positive and significant influence on work motivation. (3) work discipline has a positive and significant effect on employee performance. (4) work discipline has a positive and significant effect on work motivation. (5) work motivation has a positive and significant effect on employee performance.